MODEL DEPENDENSI HARGA-HARGA KOMODITAS EKSPOR UNGGULAN INDONESIA MENGGUNAKAN PENDEKATAN COPULA - Riri Sesiati; Jose Rizal; Yulian Fauzi (UNIVERSITAS NEGERI PADANG, 2023)
The export of non-oil and gas leading commodities (palm oil, rubber and cocoa) contributes the largest state revenue. Copula is used to model the dependency between two variables that have different marginal distributions. The data to be used is secondary data from the Commodity Futures Trading Supervisory Agency (BAPPEBTI) starting from January 1, 2018 - February 28, 2020 for the period before the Covid-19 pandemic and March 1, 2020 - November 26, 2021 for the period after the Covid-19 pandemic. The dependency of the two variables to be measured is the price of palm oil, rubber and cocoa before and after the start of the Covid-19 pandemic in Indonesia. The Copula that will be used are Joe, Gumbel, Frank, Gaussian, Clayton, and Student's t. The best Copula model obtained for palm oil and rubber dependencies is the Joe Copula, while palm oil and cocoa and cocoa rubber dependencies are the Clayton Copula.